The Battle over Pastures: The Hidden War in Afghanistan - Liz Alden Wily (Revue des Mondes Musulmans et de la Méditerranée)
Rangelands (‘pastures’) constitute a large and valuable natural resource in Afghanistan. Millions of rural people shape their agro-pastoral or pastoral livelihoods around this asset. In many ways, the territorial history of Afghanistan may be written through the lens of ancient and continuing battles between ethnic groups for possession of alpine pastures. In more recent times, this battle has centred on control of the Hindu Kush, the rich highland pastures of central Afghanistan. This paper focuses on the worsening conflict over this resource and the diminishing opportunities for its resolution, as new pressures mount. Despite numerous government initiatives, the Karzai Administration has failed to get to grips with the ownership issues underpinning this contestation and the associated seasonal armed conflict. As rangelands are made more available for purchase in the marketplace and as a surge in mining developments eats into pastures, more conflict may be expected, deepening divisions not only between ethnicities, but also between rich and poor, and between the people and the state.